Bank governance, regulation, supervision, and risk reporting: evidence from operational risk disclosures in European banks - Barakat, Ahmed; Hussainey, Khaled (Elsevier, 2013)
This paper investigates the direct and joint effects of bank governance, regulation, and supervision on the quality of risk reporting in the banking industry, as proxied for by operational risk disclosure (ORD) quality in European banks. After controlling for the endogeneity between bank stability and risk reporting quality, we find that banks having a higher proportion of outside board directors, lower executive ownership, concentrated outside non-governmental ownership, and more active audit committee, and operating under regulations promoting bank competition (i.e., less stringent entry to banking requirements) provide ORD of higher quality. In addition, we find that the contribution of bank supervisors to the enhancement of ORD quality depends on the ownership structure of the bank. Specifically, powerful and independent bank supervisors mitigate the incentives for entrenched bank executives to withhold voluntary ORD. Moreover, bank supervisors and largest shareholders perform substitutive roles in monitoring the bank management's compliance with mandatory ORD requirements. For the sake of enhancing risk reporting quality in banks, our findings recommend sustaining board independence, enhancing audit committee activity, easing entry to banking requirements, and promoting a more proactive role for bank supervisors.